PENGARUH KUALITAS PELAYANAN, PENDAPATAN, MEDIA PROMOSI, DAN LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI PADA PRODUK TABUNGAN EMAS PT PEGADAIAN UNIT CABANG WATES - Dhistya Indraswari; Faisol; Mar’atus Solikah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Investment decisions are one of the important factors in achieving future financial goals. The Gold Savings product offered by PT Pegadaian has become an attractive investment alternative due to its easy accessibility and relatively low level of risk. However, public interest in the Gold Savings product remains lower than in pawn services, which are Pegadaian’s primary business product. Therefore, it is necessary to understand the factors influencing investment decisions. Investment decisions are affected by various factors, including service quality, income, promotional media, and financial literacy. This study aims to analyze the effects of service quality, income, promotional media, and financial literacy on investment decisions regarding the Gold Savings product at PT Pegadaian Wates Branch Unit. This research employed a quantitative approach using a survey method through the distribution of questionnaires to 101 customers selected using a simple random sampling technique. Data were analyzed using Partial Least Squares (PLS) with the assistance of SmartPLS 3 software. The results indicate that service quality, income, and financial literacy have a positive and significant effect on investment decisions. These findings suggest that customers’ investment decisions are more strongly influenced by the quality of services received, their financial capability, and their level of financial understanding than by exposure to promotional media. This study implies that PT Pegadaian should improve service quality and strengthen financial education programs to encourage greater investment decisions in Gold Savings products.